THE FOREST GROWTH CYCLE IN DRY DIPTEROCARP FOREST - Dhanmanonda, Pricha (วารสารวนศาสตร์ไทย, 2022)
Determination of the process and rate of revegetation by using data on tree density, H’(a coefficient indicating the ideal maximum tree height) and aboveground biomass were investigated in the dry dipterocarp forest (DDF) at Sakaerat Environmental Research Station (SERS), Pak Thong Chai District, Nakhon Ratchasima Province, Northeastern Thailand. The results revealed that the forest growth cycle (the gap phase, the building phase and the mature phase) were estimated to be 0-60, 60-122, 122-244, Rapid increase in basal area, H’ and high mortality of sapling were found during the gap phase. A slow increase in basal area, H ’and low mortality were found during the building phase, while the mature phase was characterized by an alomst saturated basal area, H’ and above-ground bio-mass. No gap indicators occured in the study forest.